E-Governance Status in India - Dutta, Ajay; Syamala Devi, M (International Journal of Computer Sciences and Engineering, 2025)
E-governance refers to the delivery of government information and services via the Information and communications technology (ICT) to citizens or businesses or governmental agencies. The purpose of this paper is to present the status of e-Governance in India. The paper discusses the initiatives taken by Government of India to computerize Government to Citizen (G2C), Governance to Business (G2B) and Government to Government (G2G) services. The important G2C services like National Rural Employment Guarantee Scheme (NREGS) and Dial.Gov; G2B services like Ministry of Corporate Affairs and e-Biz and G2G services like SmartGov of Andhra Pradesh and e-Office are presented in detail. Tools and Technologies are adopted for providing e-Governance services are explained. The issues in digital governance like Cyber Crime and lack of Citizen Unique Identity are also mentioned. Government projects in pipeline and future projects are also included. It is concluded that e-Governance in India enables people to have efficient, effective, transparent and accountable services.